Evaluation of Blood Lactate Level as a Predictor of In-hospital Morbidity and Mortality in Patients Undergoing Surgery for Bowel Perforation: A Prospective Cohort Study - Anish Kumar Singh23; Sandeep Kumar; Nityasha, Mamta Jain; Mamta Jain; Teena Bansal; Amanpreet Singh (Journal of Clinical and Diagnostic Research)
Introduction: Perforation peritonitis is associated with significant Morbidity and Mortality (M&M). The predictive performance of blood lactate levels and their clearance varies depending on the timing of measurement, and the optimal time for measurement remains unclear.